2021
DOI: 10.7759/cureus.17255
|View full text |Cite
|
Sign up to set email alerts
|

Association Between COVID-19 Outcomes and Patient Characteristics: A Study in an Inner-City Community Hospital

Abstract: BackgroundIt has been shown that certain hematological conditions, such as lymphopenia and thrombocytopenia, are associated with increased severity and mortality from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. However, a majority of the previous data came from large institutional centers with high academic output. We aimed to explore the association between patient's characteristics, hematological parameters, and outcomes in admitted persons with coronavirus disease 2019 (COVID-19)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Thyroid disease was likewise suggestive of inferior outcomes in prior studies [ 91 , 93 ], but was not found to be significant in this study. Figure 6 depicts increasing risk in individuals with greater numbers of comorbidities, similar to an earlier report which utilized the Charlson Comorbidity Index Score (CCIS) to address similar questions [ 94 ].…”
Section: Discussionmentioning
confidence: 75%
“…Thyroid disease was likewise suggestive of inferior outcomes in prior studies [ 91 , 93 ], but was not found to be significant in this study. Figure 6 depicts increasing risk in individuals with greater numbers of comorbidities, similar to an earlier report which utilized the Charlson Comorbidity Index Score (CCIS) to address similar questions [ 94 ].…”
Section: Discussionmentioning
confidence: 75%
“…For each confirmed case, we extracted the following: 1 date of notification in the system, 2 symptom onset date, 3 age, 4 gender, 5 ethnic group, 6 location (county, city/town, and zip code), 7 occupation, 8 presence of various symptoms at the time of testing, 9 information on chronic comorbidities and 10 whether the person was hospitalized and/or died following their diagnosis. All data on symptom onset, presence of symptoms, and presence of comorbidities were self-reported by the patient and covered symptoms/comorbidities as defined in a simple questionnaire without ICD codes.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of these studies were based on data from large cities or selected population groups such as veterans, hospitalized patients or specific ethnic groups. Only a limited number of publications have used routinely collected surveillance data from smaller urban areas focusing on both hospitalized and non-hospitalized SARS-CoV-2 positive individuals 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 . In general, published evidence suggests that males are more likely to be infected, hospitalized and die from severe COVID-19 than females 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%